β-Alanine supplementation increased physical performance and improved executive function following endurance exercise in middle aged individuals - Taylor Furst; Alyssa Massaro; Courtney Miller; Brian T. Williams; Zach M. LaMacchia; Peter J. Horvath (Taylor & Francis Group, 2018)
Background Sarcopenia, a reduction in muscle mass and function seen in aging populations, may be countered by improving systemic carnosine stores via beta-Alanine (β-alanine) supplementation. Increasing systemic carnosine levels may result in enhanced anti-oxidant, neuro-protective and pH buffering capabilities. This enhancement should result in improved exercise capacity and executive function. Methods Twelve healthy adults (average age = 60.5 ± 8.6 yrs, weight = 81.5 ± 12.6 kg) were randomized and given either 2.4 g/d of β-alanine (BA) or Placebo (PL) for 28 days. Exercise capacity was tested via bouts on a cycle ergometer at 70% VO2 peak. Executive function was measured by Stroop Tests 5 min before exercise (T1), immediately before exercise (T2), immediately following fatigue (T3), and 5 min after fatigue (T4). Lactate measures were taken pre/post exercise. Heart rate, Rating of Perceived Exertion (RPE) and VO2 were recorded throughout exercise testing. Results PRE average time-to-exhaustion (TTE) for the PL and BA group were not significantly different (Mean ± SD; 9.4 ± 1.4mins vs 11.1 ± 2.4mins, respectively, P = 0.7). POST BA supplemented subjects cycled significantly longer than PRE (14.6 ± 3.8mins vs 11.1 ± 2.4mins, respectively, P = 0.04) while those given PL did not (8.7 ± 2.4mins vs 9.4 ± 1.4mins, respectively, P = 0.7). PL subjects were slower in completing the Stroop test POST at T4 compared to T3 (T3 = − 13.3 ± 8.6% vs T4 = 2.1 ± 8.3%, P = 0.04), while the BA group (T3 = − 9.2 ± 6.4% vs T4 = − 2.5 ± 3.5%, P = 0.5) was not. POST lactate production expressed a trend when comparing treatments, as the BA group produced 2.4 ± 2.6 mmol/L more lactate than the PL group (P = 0.06). Within group lactate production for BA (P = 0.4) and PL (P = 0.5), RPE (P = 0.9) and heart rate (P = 0.7) did not differ with supplementation. Conclusion BA supplementation increased exercise capacity and eliminated endurance exercise induced declines in executive function seen after recovery. Increased POST TTE coupled with similar PRE vs POST lactate production indicates an improvement in the ability of BA to extend exercise durations. Furthermore, by countering endurance exercise's accompanying deficits in executive function, the aging population can maintain benefits from exercise with improved safety.